Thromboxane and histamine mediate PVR elevation during xenogeneic pig lung perfusion with human blood. (3rd September 2018) - Burdorf, Lars; Harris, Donald; Dahi, Siamak; Laird, Christopher; Zhang, Tianshu; Ali, Franchesca; Shah, Aakash; Thompson, Mercedes; Braileanu, Gheorghe; Cheng, Xiangfei; Sievert, Evelyn; Schwartz, Evan; et al.
Abstract: Background: Elevated pulmonary vascular resistance (PVR), platelet adhesion, coagulation activation, and inflammation are prominent features of xenolung rejection. Here, we evaluate the role of thromboxane and histamine on PVR, and their contribution to other lung xenograft injury mechanisms. Methods: GalTKO.hCD46 single pig lungs were perfused ex vivo with fresh heparinized human blood: lungs were either treated with 1‐Benzylimidazole (1‐BIA) combined with histamine receptor blocker famotidine (n = 4) or diphenhydramine (n = 6), 1‐BIA alone (n = 6) or were left untreated (n = 9). Results: Six of the nine control experiments (GalTKO.hCD46 untreated), "survived" until elective termination at 4 hours. Without treatment, initial PVR elevation within the first 30 minutes resolved partially over the following hour, and increased progressively during the final 2 hours of perfusion. In contrast, 1‐BIA, alone or in addition to either antihistamine treatment, was associated with low stable PVR. Combined treatments significantly lowered the airway pressure when compared to untreated reference. Although platelet and neutrophil sequestration and coagulation cascade activation were not consistently altered by any intervention, increased terminal wet/dry weight ratio in untreated lungs was significantly blunted by combined treatments. Conclusion: Combined thromboxane and histamine pathway blockade prevents PVR elevation and significantly inhibits loss of vascular barrier function when GalTKO.hCD46 lungs are perfused with human blood. Platelet activation and platelet and neutrophil sequestration persist in all groups despite efficient complement regulation, and appear to occur independent of thromboxane and histamine antagonism. Our work identifies thromboxane and histamine as key mediators of xenolung injury and defines those pathways as therapeutic targets to achieve successful xenolung transplantation.